Impact of a Structured Social Skills Training Program on Adolescents and Young Adults with Level 1 Autism - Leonardo Zoccante; Sara Sabaini; Erika Rigotti; Sophia Marlene Bonatti; Camilla Lintas; Marco Zaffanello (Pediatric Reports)
Background/Objectives: Level 1 autism spectrum disorder (ASD) is a neurodevelopmental condition characterised by challenges in social and communication skills. Despite these difficulties, individuals with level 1 ASD often exhibit average intelligence and typical language development. Improving socialisation skills in this population requires tailored approaches that address their specific needs and include targeted strategies. This study aims to evaluate the effectiveness of a structured social skills training programme for adolescents and young adults with level 1 ASD. Methods: Participants diagnosed with level 1 ASD, regardless of gender, were consecutively recruited from an outpatient clinic. The intervention involved activities from the Social Skills, Autonomy, and Awareness Module, specifically designed for adolescents and young adults. Sessions were conducted fortnightly, lasting 1.5 to 3 h each, over 17 months. Adaptive behaviour was assessed using the Vineland Adaptive Behaviour Scales (VABS) at baseline and after completing the programme. Data were analysed with SPSS version 22.0 (SPSS Inc., Chicago, IL, USA). Statistical methods included automatic clustering to identify optimal clusters and Pearson’s Chi-square and Fisher’s exact tests to evaluate variable distributions among the clusters. Results: A total of 31 participants (77.4% female) with a mean age of 20.1 years (SD = 7.0) were included in the study. Two distinct clusters emerged. Cluster 1 (n = 8) had significantly higher mean ages and baseline Vineland II socialisation scores than Cluster 2 (n = 23). Both clusters demonstrated significant improvements in social skills following the intervention. Conclusions: This study highlights distinct profiles within individuals with level 1 ASD, showing a clear link between age and social skill development. The intervention improved social skills for most participants, regardless of the age at which treatment began. For some individuals, alternative or augmented treatment strategies may be necessary to achieve optimal results.